Deep learning and capsule endoscopy: Automatic multi-brand and multi-device panendoscopic detection of vascular lesions - Mascarenhas, Miguel; Martins, Miguel; Afonso, João; Ribeiro, Tiago; Cardoso, Pedro; Mendes, Franscisco; Andrade, Patrícia; Cardoso, Helder; Mascarenhas-Saraiva, Miguel; Ferreira, João; Macedo, Guilherme (Endoscopy International Open, 2024)
Background and study aims Capsule endoscopy (CE) is commonly used as the initial exam for suspected mid-gastrointestinal bleeding after normal upper and lower endoscopy. Although the assessment of the small bowel is the primary focus of CE, detecting upstream or downstream vascular lesions may also be clinically significant. This study aimed to develop and test a convolutional neural network (CNN)-based model for panendoscopic automatic detection of vascular lesions during CE.Patients and methods A multicentric AI model development study was based on 1022 CE exams. Our group used 34655 frames from seven types of CE devices, of which 11091 were considered to have vascular lesions (angiectasia or varices) after triple validation. We divided data into a training and a validation set, and the latter was used to evaluate the model’s performance. At the time of division, all frames from a given patient were assigned to the same dataset. Our primary outcome measures were sensitivity, specificity, accuracy, positive predictive value (PPV), negative predictive value (NPV), and an area under the precision-recall curve (AUC-PR).Results Sensitivity and specificity were 86.4% and 98.3%, respectively. PPV was 95.2%, while the NPV was 95.0%. Overall accuracy was 95.0%. The AUC-PR value was 0.96. The CNN processed 115 frames per second.Conclusions This is the first proof-of-concept artificial intelligence deep learning model developed for pan-endoscopic automatic detection of vascular lesions during CE. The diagnostic performance of this CNN in multi-brand devices addresses an essential issue of technological interoperability, allowing it to be replicated in multiple technological settings.
Keywords: Small bowel endoscopy; Small intestinal bleeding; Endoscopy Upper GI Tract; Non-variceal bleeding; Endoscopy Lower GI Tract; Lower GI bleeding